Influence of speed and heel-to-toe drop in running shoes for female recreational runners: A cross-sectional study. - Gijón-Noguerón, Gabriel; Soler-Crespo, Francisco José; Sanchez-Rodriguez, Raquel; Cabello-Manrique, David; Lópezosa-Reca, Eva; Ortega-Ávila, Ana Belén (Wolters Kluwer Health, 2019)
In recent years, the popularity of running has boomed and the number of women runners has risen sharply. However, little research has been conducted into the running cycle as concerns female runners. The aim of this study is to analyse, in women runners, the relationships between spatiotemporal parameters in the running cycle, the heel drop in running shoes and a progressive increase in training speed, when running on a treadmill. Thirty-eight female runners were recruited from the Malaga University Athletics Club and Nerja Athletics Club. All were at least 18 years old, recreationally active (3–4 running sessions per week) and able to run 5kmin less than 25min. Their running performance on a treadmill was recorded and spatiotemporal parameters assessed using the OptoGait system. As the running speed increased (8–12–15km/h) the spatiotemporal parameters of the running cycle altered: the flight time increased (P<.001) and the contact time decreased (P=.05). Heel drop (4–12mm) was not significantly associated with any of the parameters (phase 1: P=.198; phase 2: P=.191; phase 3: P=.242). A progressive increase in training speed on a treadmill directly influences the spatiotemporal parameters of the running cycle in women runners.
Keywords: Running - Equipos y material; Calzado deportivo; Deportes femeninos - Entrenamiento; Female runners; Heel-to-toe drop; Running; Spatiotemporal parameters; Speed